Students and the perception about the High School's functions (Research, Society and Development, 2021)
This paper presents the results of a research that aimed to characterize the perception of students about the importance of the school training them for the high school objectives recommended by the Law of Education’s Guidelines and Bases (LDB). The research included 534 students from the cities of Juazeiro do Norte (CE), Fortaleza (CE) and São Paulo (SP), from the 3rd year of high school in public, private and vocational schools and public and private pre-university preparatory courses. The results showed that 97.9% of them considered it important that the school could prepare them to continue their studies, and when questioned about how the school prepared them for these features, the work was the point that the students felt less prepared for (75.4%). The results highlighted the importance of understanding the perception of youth about this subject, since according to them the school has not been able to fulfill its objectives.